Visual short-term memory deficits associated with GBA mutation and Parkinson's disease. (11th June 2014) - Zokaei, Nahid; McNeill, Alisdair; Proukakis, Christos; Beavan, Michelle; Jarman, Paul; Korlipara, Prasad; Hughes, Derralynn; Mehta, Atul; Hu, Michele T. M.; Schapira, Anthony H. V.; Husain, Masud
Abstract : Individuals with mutation in the lysosomal enzyme glucocerebrosidase ( GBA ) gene are at significantly high risk of developing Parkinson's disease with cognitive deficit. We examined whether visual short-term memory impairments, long associated with patients with Parkinson's disease, are also present in GBA -positive individuals—both with and without Parkinson's disease. Precision of visual working memory was measured using a serial order task in which participants observed four bars, each of a different colour and orientation, presented sequentially at screen centre. Afterwards, they were asked to adjust a coloured probe bar's orientation to match the orientation of the bar of the same colour in the sequence. An additional attentional 'filtering' condition tested patients' ability to selectively encode one of the four bars while ignoring the others. A sensorimotor task using the same stimuli controlled for perceptual and motor factors. There was a significant deficit in memory precision in GBA -positive individuals—with or without Parkinson's disease—as well as GBA -negative patients with Parkinson's disease, compared to healthy controls. Worst recall was observed in GBA -positive cases with Parkinson's disease. Although all groups were impaired in visual short-term memory, there was a double dissociation between sources of error associated with GBA mutation and Parkinson's disease. The deficit observed in GBA -positive individuals, regardless of whether they had Parkinson's disease, was explained by a systematic increase in interference from features of other items in memory: misbinding errors. In contrast, impairments in patients with Parkinson's disease, regardless of GBA status, was explained by increased random responses. Individuals who were GBA -positive and also had Parkinson's disease suffered from both types of error, demonstrating the worst performance. These findings provide evidence for dissociable signature deficits within the domain of visual short-term memory associated with GBA mutation and with Parkinson's disease. Identification of the specific pattern of cognitive impairment in GBA mutation versus Parkinson's disease is potentially important as it might help to identify individuals at risk of developing Parkinson's disease.